Athletes' health care services in the Finnish sports academies - Hietala, Henni (2015)
In today´s top-level sport environment, requirements to achieve success are demanding and athletic competition has totalized into a competition between sport systems. In order to keep up in this race, sport in Finland has recently been under intense organizational construction and development. As one of the three strategic components of the Finnish elite sport system, Sports Academy Program serves aspiring young athletes to combine studies with sport, and offers diverse services to support their careers, including athletes´ health care services.